Faktor-Faktor yang Berhubungan dengan Motivasi Lansia Berpartisipasi di Program Olahraga Rutin Posyandu Lansia Permata - Hellen Tryani Mone Ke; Ernawati Ernawati (Faletehan Health Journal, 2022)
The aging process causes various changes and decrease of body organs function. To inhibit the decline of body functions and to lessen risks of diseases, elders need to do physical exercises. Besides, the exercises are also able to support their emotional and mental. Thus, it will impact on the quality of life of elderly. However, previous studies found that there were many barriers that cause elderly reluctant to do exercises. This study aimed to determine the factors relating to the motivation of elderly in exercising at Permata Integrated Health Post (Posyandu), Kelapa Lima Village, Kupang. The research design was descriptive correlative with a cross-sectional approach. The data collection technique used total sampling. The respondents were 57 elders whose age were 60 years old and over. The study showed that there was a relationship between sex (p-value = 0.019), education level (p-value = 0.000) and barriers to the motivation of the elderly to exercise (p-value = 0.032). However, there was no relationship between age (p-value = 0.417) and work status with the motivation of the elderly to exercise (p-value = 0.809). Further research was suggested to examine other factors relating to the motivation of the elderly in exercising such as knowledge, economic conditions, family support, and the benefits of exercise.